1)
0\\ x<5\\ 2^0=5-x\\ 1=5-x\\ x=4" alt="\\\log_2(5-x)=0\\ 5-x>0\\ x<5\\ 2^0=5-x\\ 1=5-x\\ x=4" align="absmiddle" class="latex-formula">
2)
0 \wedge x-1>0\\ x>0 \wedge x>1\\ x>1\\ \lg5x(x-1)=1\\ 10^1=5x^2-5x\\ 5x^2-5x-10=0\\ 5x^2+5x-10x-10=0\\ 5x(x+1)-10(x+1)=0\\ 5(x-2)(x+1)=0\\ x=2 \vee x=-1\\ -1\not>1 \Rightarrow x=2\\ " alt="\\\lg 5x+\lg(x-1)=1 \\ 5x>0 \wedge x-1>0\\ x>0 \wedge x>1\\ x>1\\ \lg5x(x-1)=1\\ 10^1=5x^2-5x\\ 5x^2-5x-10=0\\ 5x^2+5x-10x-10=0\\ 5x(x+1)-10(x+1)=0\\ 5(x-2)(x+1)=0\\ x=2 \vee x=-1\\ -1\not>1 \Rightarrow x=2\\ " align="absmiddle" class="latex-formula">